Supervisi Manajerial Pengawas Sekolah untuk Meningkatkan Kinerja Guru dalam Mengolah Administrasi Pembelajaran Rencana Pelaksanaan Pembelajaran di Sekolah Dasar - Yuliani Widyastuti (Jurnal Pendidikan Dasar, 2020)
Abstract. The purpose of this study was to determine the increase in teacher performance in managing the learning administration "Learning Implementation Plan" (RRP) through managerial supervision of school supervisors at SD Negeri Sikepan 1, Srumbung District, Magelang Regency. This type of research is a study that uses a school action research (PTS) design with a qualitative approach. The research subjects in this study were 6 class teachers at SD Negeri Sikepan 1, Srumbung District, Magelang Regency. The main data were obtained from the class teacher. Data collection methods by interview, observation, and documentation methods.The results showed that managerial supervision was able to improve the performance of class teachers at SD Negeri Sikepan 1, Srumbung District, Magelang Regency in managing learning administration. Learning Implementation Plan (RPP) in quality and quantity. The teacher's performance in managing learning administration, the Learning Implementation Plan (RPP) only reached a percentage of 60.42% (there were 3 teachers in the bad category and 3 teachers in the good category), after being given the action it increased in cycle I to 72.92% (there is 1 person, the teacher is in the bad category, 3 teachers are in the good category and 2 teachers are in the very good category) and in the second cycle it increases to 85.42% (there are 2 people in the good category and 4 teachers in the good category)